Coming Full Circle: Why Social and Institutional Dimensions Matter for the Circular Economy. (28th April 2017) - Moreau, Vincent; Sahakian, Marlyne; van Griethuysen, Pascal; Vuille, François
Summary: In light of the environmental consequences of linear production and consumption processes, the circular economy (CE) is gaining momentum as a concept and practice, promoting closed material cycles by focusing on multiple strategies from material recycling to product reuse, as well as rethinking production and consumption chains toward increased resource efficiency. Yet, by considering mainly cost‐effective opportunities within the realm of economic competitiveness, it stops short of grappling with the institutional and social predispositions necessary for societal transitions to a CE. The distinction of noncompetitive and not‐for‐profit activities remains to be addressed, along with other societal questions relating to labor conditions, wealth distribution, and governance systems. In this article, we recall some underlying biophysical aspects to explain the limits to current CE approaches. We examine the CE from a biophysical and social perspective to show that the concept lacks the social and institutional dimensions to address the current material and energy throughput in the economy. We show that reconsidering labor is essential to tackling the large share of dissipated material and energy flows that cannot be recovered economically. Institutional conditions have an essential role to play in setting the rules that differentiate profitable from nonprofitable activities. In this context, the social and solidarity economy, with its focus on equity with respect to labor and governance, provides an instructive and practical example that defies the constraints related to current institutional conditions and economic efficiency. We show how insights from the principles of the social and solidarity economy can contribute to the development of a CE by further defining who bears the costs of economic activities.